Validation of 2D force measurement roller ski and practical application - Zhao, S.; Linnamo, V.; Ruotsalainen, K.; Lindinger, S.; Kananen, T.; Koponen, P.; Ohtonen, O. (9th International Congress on Science and Skiing, March 18 - 22, 2023, Saalbach-Hinterglemm, Austria, 2023)
INTRODUCTION: Several methods could measure the forces from ski or roller skis in cross-country skiing (Othonen et al., 2013; Hoset et al., 2014). Equipment which could measure medio-lateral forces may be of good help for investigating the relevant skating techniques. The aim of this study was to validate a pair of newly designed 2-dimensional force measurement roller skis. The vertical and medio-lateral forces which were perpendicular to the body of the roller ski could be measured.